Portuguese scientific output on Web of Science and on Scopus: a comparative analysis - Costa, Teresa; Lopes, Carlos; Vaz, Francisco (Qualitative and Quantitative Methods in Libraries, 2015)
In 2004 the Portuguese library consortium, Online Knowledge Library (b-on), was launched and with it, it became easier to get access to full text international scientific publications. This study aims to analyse some bibliometric indicators of the Portuguese scientific output seeking to evaluate the correlation with b-on. It was analysed the usage of b-on resources by the public universities members of the consortium from 2004 to 2010, with a sample of the five universities with more downloads per FTE (full time equivalent).In addition to the usage data, we analysed the Portuguese scientific output  through the comparison of two databases: Web of Science (WoS) from Thomson Reuters and Scopus from Elsevier from which we identified the articles indexed with Portuguese affiliation and by the five Portuguese universities between 2000-2010. The study confirms that the availability and access to electronic resources contributes to the increased of the scientific productivity of the universities and that the study and analysis of its use and output are essential